Comparing Diagnostic Value of Renal Parenchymal Resistive Index And Cortical Echogenicity in Chronic Kidney Disease Patients - Sutikno, Dria Anggraeny; Baskoro, Nurdopo (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: Chronic kidney disease (CKD) is a clinically impaired kidney degradation syndrome, which commonly is diagnosed based on glomerulus filtration rate (GFR). Renal parenchymal resistive index and the renal cortex echogenicity are ultrasound parameters that have been reported correlate with GFR values. This study aims to determine the sensitivity, specificity, positive predictive value, and negative predictive value between renal intra-parenchymal resistive index and renal cortical echogenicitybased on GFR in CKD patients. Materials and Methods: This study is a cross sectional design. A renal ultrasound examination was performed to forty one CKD patients to assess the resistive index of the renal intra-parenchymal artery and the echogenicityof the renal cortex. The creatinine serum levels were obtained from the patients, as the gold standard of CKD diagnosis. Statistical data processing uses diagnostic test and Inter class Correlation Coefficients (ICC). Results: The sensitivity, specificity, positive predictive value, and negative predictive value of renal intraparenchymal resistive indexes were 23%, 79%, 33%, and 69% respectively. Sensitivity, specificity, positive predictive value, and negative predictive value between renal cortex echogenicity were 23%, 96%, 75%, and 73% respectively. The ICC analysisreported a Single Rater value of 0.1538 and Average of Raters 0.3528. Conclusion: Renal intra-parenchymal resistive artery was more specific than renal cortex echogenicity for diagnosing patients with chronic kidney disease. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 194-199